Hydrocephalus outcome: validation of endoscopic third ventriculostomy success score. (4th April 2011) - Durnford, A J; Kirkham, F J; Mathad, N; Sparrow, O; Rodgers, W
Abstract : Aims: To externally validate the Endoscopic Third Ventriculostomy Success Score (ETVSS) recently found by Kulkarni et al 1 to predict successful ETV for hydrocephalus, that is, child not requiring shunt or repeat ETV, on the basis of a child's individual characteristics. The ETVSS is based upon patient age, aetiology and presence of a previous shunt. To date there has been no external validation of this model. We consider both short term and long term outcome, using a detailed large single centre series of paediatric patients with a long period of follow-up. Methods: We retrospectively identified consecutive children undergoing ETV at a single regional neurosurgery centre. We compared actual success at both 6 and 36 months with mean predicted probabilities for low, moderate and high chance of success strata based on the ETVSS. Long-term success was calculated using Kaplan Meier methods and comparisons made by unpaired t tests. Results: In total 166 primary ETV were performed at a median age of 39 (range 0.03–230) months. There was a greater number of patients in younger age groups in this series; 49 patients were under 6 months of age (29.5%) compared to 129 (20.9%) in the model dataset (difference 8.6%, CI 1.0 to 16.3; p=0.07). Overall, ETV success was 72.9% at 6 and 64.5% at 36 months. Although derived to predict outcome at 6 months, the model predicted outcome better on long-term follow-up than at 6 months. At long-term follow-up, the mean predicted probability was significantly higher in those with a successful ETV (n=99) than in those who failed (n=67) (p=0.001). The ETVSS accurately predicted long term success rates; the low, medium and high groups had mean predicted probabilities of 82%, 63% and 36% and overall success at 36 months of 76%, 66%, 42% respectively. The overall complication rate was 6%. Conclusion: The ETVSS closely predicted the overall long term success rates in high, moderate and low risk groups. Our study suggests the ETVSS will be useful in the clinical decision-making in predicting long term outcome of ETV but further refinement of the model, validation and comparison with shunt treatment is required.